2007
DOI: 10.1016/j.jinteco.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Trade liberalization and rising wage inequality in Latin America: Reconciliation with HOS theory

Abstract: The paper puts forward the hypothesis that the transitory effects of trade liberalization on wage inequality can differ from the long-run outcome. In cases where the HOS theory predicts a decline in wage inequality in the long run, a temporary rise can, nevertheless, occur due to (i) the asymmetries in the speed of contraction in the import sector and expansion in other sectors, and (ii) the capital-skill complementarity in production. The asymmetric contraction and expansion causes a transitory capital accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
1
13
0
7
Order By: Relevance
“…There are, however, some tentative theoretical explanations for the pattern. For example, Atolia (2007) has suggested that, under certain circumstances, even if the standard prediction from a Hecksher-Ohlin-Samuelson model works as predicted in the long-run, there may be some short-run (or transitory) effects of trade liberalization that may lead to a different outcome from those of the long-run. The difference between short-run and long-run effects on inequality result from two factors: first, an asymmetry in the contraction and expansion of some sectors, and second, because of the capital-skill complementarity in production.…”
Section: Concluding Remarks: the Rise And Fall Of Income Inequality Amentioning
confidence: 99%
“…There are, however, some tentative theoretical explanations for the pattern. For example, Atolia (2007) has suggested that, under certain circumstances, even if the standard prediction from a Hecksher-Ohlin-Samuelson model works as predicted in the long-run, there may be some short-run (or transitory) effects of trade liberalization that may lead to a different outcome from those of the long-run. The difference between short-run and long-run effects on inequality result from two factors: first, an asymmetry in the contraction and expansion of some sectors, and second, because of the capital-skill complementarity in production.…”
Section: Concluding Remarks: the Rise And Fall Of Income Inequality Amentioning
confidence: 99%
“…13 See Acemoglu (2002) and Card and Di Nardo (2006), among others. 14 See also Acemoglu (2003), Atolia (2007) and Yeaple (2005).…”
mentioning
confidence: 99%
“…While such a model rationalizes our findings, other modeling frameworks with factor specificity are likely to play a role as well. In addition, Atolia (2007) develops an alternative model with capital complementarity of skills that would also allow for a reconciliation of HOS theory. The ultimate lesson is that the Stolper-Samuelson effects predicted for Latin America are found to play a role in shaping the wage distribution, but only after the incorporation of some mechanism for inter-industry wage differences.…”
Section: Discussionmentioning
confidence: 99%